IDENTIFIKASI DAN ANALISIS KADAR FLAVONOID EKSTRAK GETAH ANGSANA (Pterocarpus indicus Willd) DI DUSUN WANATH KECAMATAN LEIHITU KABUPATEN MALUKU TENGAH - Nurmila Nurmila; H Sinay; Theopilus Watuguly (BIOPENDIX, 2019)
Background: Medicinal plants have many benefits that make it a traditional medicine for society. One of the medicinal plants used by the community, especially the Wanath Hamlet community, is the angsana gum (Pterocarpus indicus Willd.) In treating diseases. Method: This study aims to identify and analyze flavonoid levels in angsana sap (Pterocarpus indicus Willd.) In Wanath Hamlet qualitatively (flavonoid color test) and quantitative (flavonoid content analysis). Results: The results show a change in color to yellow which indicates that the sap is positive for flavonoids, while in aquades it shows clear color changes which indicate negative. Conclusion: Qualitative test (color test) of angsana gum extract positively contains flavonoids when identified with several flavonoid reagents which produce yellow